Mixed-income housing developments as a social and spatial integration strategy: the case of Fleurhof integrated residential development - Sibanda, Amanda (University of the Witwatersrand, School of Architecture and Planning, 2017)
The development of sustainable human settlements advocated in the 2004 Breaking New Ground-A Comprehensive Plan for the Development of Sustainable Human Settlements has brought attention to the significance and meaning of integration. Mixed-income housing developments along with informal settlements upgrading are two approaches South Africa’s local governments have implemented to address rapid urbanisation and the urban housing demand that has proven to be a challenge in South Africa. The rationale behind these two approaches has been to address the increasing challenge of urban poverty, urban redevelopment and the entrenched issue of socio-spatial segregation. Social and spatial segregation are challenges the City of Johannesburg has been facing and are in constant battle to address. Urban spatial policies express the requirement for social and spatial integration in the city in order to achieve the overarching vision of becoming a sustainable socially inclusive compact city. Mixed-income housing developments have been touted as an approach that can achieve the implementation of social and spatial integration of urban neighbourhoods. They are seen as a method to integrating the urban poor, low-income individuals and families into the societal structures that will assist them in their upward drive in the economic ladder and influence their social behaviour, combating the social ills and notions of public housing; and addressing the spatial segregation of land use, transport and human settlements. The purpose of this research is to explore mixed-income housing development with the objective of socio-spatial integration and investigate the structures of social interactions. The case study for this research is Fleurhof Integrated Residential Development-a private-public mixed-income housing development located south-west of Johannesburg Central Business District. This research aims to investigate the processes and methods of social integration in Fleurhof and the ability of this development in achieving spatial integration.
A research report submitted to the Faculty of Engineering and Built Environment at the University of Witwatersrand, in partial fulfillment to the requirements for the Bachelor of Science (Honours) in Urban Regional Planning Degree.
Keywords: Mixed-income housing--Informal settlements; Sustainable human settlements; Social and spatial integration; Informal settlement upgrading